2007
DOI: 10.1021/ma070181q
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation Study of Amphiphilic ROMP Block Copolymers by SAXS and TEM

Abstract: The self-assembly of block copolymers to form well-ordered structures is of great interest for the design of hierarchical materials. In this contribution, the morphologies and properties of well-defined block copolymers with narrow molecular weight distributions prepared by ring-opening metathesis polymerization are studied. Two series of amphiphilic AB-block copolymers poly [(endo,exo[2.2.1]bicyclohept-5-ene-2,3-dicarboxylic acid dimethyl ester)-b-(endo,exo[2.2.1]bicyclohept-5-ene-2,3-dicarboxylic acid)] of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…In almost all cases, their water solubility is due to the chemical functionalities on the polymer backbone. We and others have previously reported water‐soluble polymers containing noncharged poly(ethylene oxide) (PEO) side chains, as well as positively charged and zwitterionic water‐soluble polymers, all of which were obtained by ring‐opening metathesis polymerization (ROMP) 5–11. Here, we complement these previous papers with this report on a well‐defined polymer obtained from ROMP, which bears two carboxylic acid groups per repeat unit.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In almost all cases, their water solubility is due to the chemical functionalities on the polymer backbone. We and others have previously reported water‐soluble polymers containing noncharged poly(ethylene oxide) (PEO) side chains, as well as positively charged and zwitterionic water‐soluble polymers, all of which were obtained by ring‐opening metathesis polymerization (ROMP) 5–11. Here, we complement these previous papers with this report on a well‐defined polymer obtained from ROMP, which bears two carboxylic acid groups per repeat unit.…”
Section: Introductionsupporting
confidence: 59%
“…Early attempts by Harrison and Feast19 to polymerize the norbornene dicarboxylic acid monomer (using ROMP with transition metal salts in aqueous media) led to broad polydispersities and yielded only low molecular weights. Later, other groups used the popular ruthenium‐based catalysis developed by Grubbs to obtain the desired poly( exo,exo ‐5‐norbornene‐2,3‐dicarboxylic acid) or one of its stereoisomers with reasonably narrow polydispersities and good molecular weight control 11, 20, 21. However, they were using protection–deprotection chemistry, which added further steps and thus cost to the polymer synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Trimmel and coworkers demonstrated that symmetrical diblock polynorbornenes derived from 3 and endo,exo - 4 cast from THF, a nonselective solvent, form lamellar nanostructures. 31 In our system, however, the grafting-from step is inefficient with endo,exo - 4 (SI, Figure S26), so we employed exo,exo - 4 . 32 It is well known that the crystallization of P3HT interferes with block copolymer self-assembly, resulting in nanofibrillar structures.…”
mentioning
confidence: 99%
“…The d-spacing observed by SAXS (41 nm for P2-OH and 35 nm for P3-OH ) is consistent with AFM observations, and greater than the spacing for the diblock alone (29 nm). 31 …”
mentioning
confidence: 99%
“…In this context, ROMP is a versatile method as it allows us to prepare a variety of amphiphilic block copolymers by choosing the functional groups, by varying the block size and by preparing di, tri, tetra-(and more) block copolymers [65]. Therefore these amphiphilic block copolymers possess self-assembly properties as shown recently [66,67]. They are also potential candidates for the texturation of hybrid organic-inorganic materials, and we have started to analyse their interaction with Al precursors.…”
Section: Block Copolymersmentioning
confidence: 99%